Direito fundamental ao ambiente ecologicamente equilibrado enquanto elemento indispensável da dignidade da pessoa humana - Trindade, Sérgio Carvalho (My University, 2014)
The present study has as purpose the environmental quality within itself as a requirement for a life grounded in one of the foundations of the Constitution, that is: the dignity of the human person. Therefore it is necessary to enter into some specificities of the dignity of the human person principle specially concerning its treatment by the Republican Letter of 1988 as well as defending the environmental protection as a fundamental human right. In the context of a globalized society in which the increasing concern with economic development occurs at the expense of conserving the environmental heritage, it is imperative that public policies are adopted in order to guarantee the so proclaimed fundamental right to an ecologically balanced environment. The work has as scope to briefly expose the fundamentality aspects of the right to the environment under the legal constitutional bias with the intent of instigating some axiological order questionings which gravitate towards the theme, in the light of what the Constitution of 1988.
O presente estudo tem por objeto a qualidade ambiental como requisito para uma vida pautada em um dos fundamentos da Constituição, qual seja: a dignidade da pessoa humana. Necessário se faz, pois, adentrar algumas especificidades do princípio da dignidade da pessoa humana, sobretudo no que concerne ao seu tratamento pela Carta Republicana de 1988, bem como defender a proteção ambiental como direito humano fundamental. No contexto de uma sociedade globalizada em que a crescente preocupação com o desenvolvimento econômico se dá em detrimento da conservação do patrimônio ambiental, é imperioso que sejam adotadas políticas públicas garantidoras do tão apregoado direito fundamental ao meio ambiente ecologicamente equilibrado. O trabalho tem por escopo expor sucintamente os aspectos da fundamentalidade do direito ao ambiente sob o viés jurídico-constitucional, no intuito de que sejam instigados alguns questionamentos de ordem axiológica que gravitam em torno do tema, à luz do que preceitua a Constituição de 1988.
Keywords: Direito; Dignidade da pessoa humana; Meio ambiente equilibrado; Fundamentalidade; Solidariedade; Brasil. Constituição (1988); Direitos fundamentais; Ecologia humana; Dignity of the human person; Balanced environment; Fundamentality; Solidarity; Brazil. Constitution (1988); Civil rights; Human ecology